Nigerian capitalism - Schatz, Sayre P. (Berkeley : University of California Press, 1977)
This book is about Nigerian economy, Early nurture- capitalism.
Includes bibliographical references and index.
oo 03/03/2018
Loans
Keywords: Industrial policy; Nigeria